Fuel for Dominance - Sulowski, Stanislaw; Sulowski, Stanislaw (Peter Lang, 2020)
The book attempts to assess the role of three economic areas in creating power in international relations, i.e. energy sector, internationalization of currency and technologies with a military significance, which might potentially become ?fuel for dominance? and an instrument to gain geopolitical advantages of great pow-ers. The book focuses on the policies of chosen countries (USA, China, Germany, and Russia) as well as the European Union in these three economic areas. The purpose is to research the manner and conditions in which the above-mentioned policies can cause the power to grow.